Aggressive surgical palliation for advanced girdle tumours - Andrew Burd; KC Wong; Shekhar M. Kumta (Indian Journal of Plastic Surgery)
Background: The surgical management of advanced, incurable, malignant disease presents particular ethical and technical challenges. The clear goal is palliation and the surgical futility must be avoided. This case series presents some particular challenges in end-of-life surgery. Materials and Methods: Fifteen patients referred with advanced malignant disease involving a limb girdle were reviewed. Results: In one case, a patient pleaded for surgery after initially requesting a delay to seek treatment from a Chinese Traditional Herbalist. The increase in tumour bulk led to problems with surgery and the patient died in a hospital a few weeks later. This case illustrates ′futility′ not recognized and encountered. The remaining 14 patients exhibited positive palliation with improved quality of dying and appreciation expressed by patients, relatives and staff. Conclusion: In selected cases, with a skilled and experienced surgical team, patients with advanced malignant disease can still benefit from aggressive surgical palliation. The margin of error is small between palliation being attempted and futility being achieved. This considerably adds to the challenge of end-of-life surgery.